1990
DOI: 10.1002/jnr.490250412
|View full text |Cite
|
Sign up to set email alerts
|

Method for isolation of kappa‐opioid binding sites by dynorphin affinity chromatography

Abstract: A kappa-opioid receptor subtype was purified from a digitonin extract of frog brain membranes, using affinity chromatography. The affinity resin was prepared by coupling dynorphin (1-10) to AH Sepharose 4B. The purified receptor binds 4,750 pmol [3H]ethylketocyclazocine (EKC) per mg protein (5,600-fold purification over the membrane-bound receptor) with a Kd of 9.1 nM. The addition of cholesterol-phosphatidylethanolamine (2:1) enhanced 3.6-fold the binding activity of the purified material, which gives a purif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Biochemical and receptor isolation studies using amphibian brain tissues demonstrated a high proportion of opioid receptors compared to mammals (131134). These reports and many others examining opioid binding sites using the European water frog, Rana esculenta , were produced from the Hungarian research group headed by Wolleman, Simon, Borsodi, and Benyhe (135142). One of the salient findings from this body of work is that amphibian brain expresses kappa -like opioid binding sites, as its competitive binding profile was most correlated to the selectivity profile of the mammalian kappa opioid receptor.…”
Section: Opioid Receptors In Non-mammalian Vertebratesmentioning
confidence: 99%
“…Biochemical and receptor isolation studies using amphibian brain tissues demonstrated a high proportion of opioid receptors compared to mammals (131134). These reports and many others examining opioid binding sites using the European water frog, Rana esculenta , were produced from the Hungarian research group headed by Wolleman, Simon, Borsodi, and Benyhe (135142). One of the salient findings from this body of work is that amphibian brain expresses kappa -like opioid binding sites, as its competitive binding profile was most correlated to the selectivity profile of the mammalian kappa opioid receptor.…”
Section: Opioid Receptors In Non-mammalian Vertebratesmentioning
confidence: 99%
“…Three major classes of opioid receptors designated μ, δ and κ have been cloned and identified as members of the G protein family of seven transmembrane domain receptors which are negatively coupled to adenylate cyclase [1–6]. Extensive efforts in the past were made by several investigators to purify the receptor proteins for elucidating their molecular properties [7–10]. However, all such attempts in the last two decades to obtain adequate amounts of homogeneous and functionally competent receptor proteins have been, by and large, unsuccessful.…”
Section: Introductionmentioning
confidence: 99%
“…In this study we found that the apparent molecular mass of rKOR was 42 and 52 kDa, based on SDS/PAGE migration. Simon et al (1990) reported that the kappa receptor purified from frog brain appeared on SDS/PAGE to have a mass of 65 kDa. The theoretical molecular weight of FLAG-tagged rKOR without any post-translational modifications is 43,612 Da.…”
Section: Discussionmentioning
confidence: 99%